High-strength corrosion-resistant white copper pipe and preparation method thereof
Patent Information
- Application Number
- CN202611429008.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-15
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]本发明针对上述的不足,提供一种高强耐蚀白铜管及其制备方法,通过合金成分优化与多步织构调控工艺,使白铜管形成特定再结晶织构,将内外表面电位差控制在≤0.06V,解决了现有技术中因电位差大导致电偶腐蚀严重、耐蚀性不足的问题
[0025]一、铸态组织均匀性的有效控制
Smart Images

Figure CN122955889A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of non-ferrous metal processing technology, specifically to a high-strength corrosion-resistant cupronickel tube and its preparation method. Background Technology
[0002] Cupronickel is a type of copper alloy with copper as the base and nickel as the main alloying element. Due to its excellent resistance to seawater corrosion and good processing and forming properties, it is widely used in marine engineering equipment such as ship seawater pipelines, condensers, heat exchangers, and offshore oil drilling platforms. Among them, BFe30-1-1 iron-copper cupronickel (also known as B30 cupronickel), with a nickel content of approximately 30%, possesses high strength, good plasticity, and excellent seawater corrosion resistance, making it the preferred material for key pipelines in the marine engineering field. However, as my country's marine engineering equipment develops towards larger scale, longer service life, and higher reliability, ship seawater pipeline systems, deep-sea exploration equipment, and offshore platforms are placing more stringent requirements on the comprehensive performance of cupronickel pipes. In actual service, BFe30-1-1 cupronickel pipes still suffer from corrosion failures; localized corrosion, pitting corrosion, and stress corrosion cracking occur frequently, seriously affecting the operational safety and service life of the equipment. Taking the oil cooler of a coastal power plant as an example, the newly replaced B30 cupronickel tubes developed serious corrosion problems shortly after being put into use; in another case, BFe30-1-1 cupronickel alloy condenser tubes experienced corrosion perforation within less than a year of being put into use. Therefore, how to further improve the corrosion resistance of B30 cupronickel while maintaining its excellent comprehensive performance has become a key technical problem that urgently needs to be solved in the current research field of cupronickel tubes.
[0003] To address the aforementioned technological needs, numerous researchers and enterprises have undertaken research and development work on cupronickel tubes and their preparation methods. Regarding alloy composition, Chinese invention patent CN103740977B discloses a corrosion-resistant cupronickel tube for marine applications and its preparation method. Its chemical composition, by weight percentage, is: carbon ≤0.03%, silicon 0.10–0.20%, manganese 6.0–8.0%, sulfur ≤0.005%, phosphorus 0.15–0.20%, nickel 22.0–24.0%, cobalt 2.0–4.0%, zinc 2.0–4.0%, lead 0.20–0.40%, iron 3.0–4.0%, rare earth elements 0.15–0.20%, arsenic 0.005–0.010%, with the balance being copper. This patent employs a process flow including melting and casting, sawing, water-sealed extrusion, tube rolling, disc stretching, disc die peeling, disc stretching, Schumacher combined drawing machine stretching, straight bar stretching, and annealing. This solves the problem of low plasticity and difficulty in adapting to coil stretching production methods in traditional copper-nickel alloy materials. Regarding tube production methods, Chinese invention patent application CN110961485A discloses a method for producing seamless large-diameter cupronickel tubes. Using BFe30-1-1 cupronickel alloy as raw material, the process involves heating ingots to 940–980℃, extruding into billet tubes, pickling, cleaning of structural defects, rolling, multi-pass stretching cold working, and annealing, achieving the production of large-diameter seamless cupronickel tubes. Furthermore, Chinese invention patent CN105312353B proposes a short-process production method for large-diameter thin-walled cupronickel tubes. This method uses a hot-cold combined mold horizontal continuous casting process to directly produce large-diameter cupronickel tube billets, which are then stretched or reduced in diameter, reducing the need for extrusion equipment and pickling processes.
[0004] Although the existing technologies have made some progress in the composition design and manufacturing process of cupronickel tubes, the following shortcomings still exist. First, existing cupronickel tube manufacturing processes mainly focus on the forming efficiency and dimensional accuracy of the tubes, with insufficient attention paid to the active control of the tube's microstructure. During hot processing such as extrusion, cold drawing, and annealing, cupronickel tubes develop specific crystallographic textures, and the type and distribution of these textures have a significant impact on the electrochemical behavior and corrosion resistance of the material. Studies have shown that controlling the recrystallization annealing process can optimize the distribution of grain boundary characteristics in copper alloys, thereby improving corrosion resistance. However, there is currently no systematic technical solution in the existing technologies for improving the seawater corrosion resistance of cupronickel tubes by controlling the recrystallization texture type. Second, the quality evaluation of existing cupronickel tubes mainly focuses on mechanical properties and geometric dimensions, with insufficient attention paid to the electrochemical uniformity of the inner and outer surfaces of the tube. During service, differences in processing deformation history and heat treatment conditions between the inner and outer surfaces of the cupronickel tube may lead to inconsistent electrochemical behavior. The resulting potential difference can exacerbate localized galvanic corrosion and accelerate the tube's failure process. There are no reports in the existing technologies regarding using the potential difference between the inner and outer surfaces of the tube as a control indicator for the corrosion resistance of cupronickel tubes. Third, the existing manufacturing processes for cupronickel tubes mostly employ traditional semi-continuous casting of solid ingots, piercing and extrusion, and multi-pass stretching, resulting in a long process and low yield. Although the short-process production process simplifies the process to some extent, it lacks precise control over solidification conditions in the continuous casting process, making it difficult to ensure the uniformity of the as-cast structure and the acquisition of fine grains, which in turn affects subsequent processing and the overall performance of the final product.
[0005] To address the shortcomings of the existing technology, this application provides a high-strength, corrosion-resistant cupronickel tube and its preparation method. Regarding the alloy composition, this application employs a multi-element composite alloying system similar to B30 cupronickel, including Ni, Co, Zn, Mn, and Fe, and further optimizes corrosion resistance through the trace addition of rare earth elements and arsenic. Regarding the preparation method, this application introduces thermodynamic data from a multi-phase phase diagram calculated using the CALPHAD method during the horizontal continuous casting process to precisely control the solidification conditions of the alloy, obtaining a uniform composition and refined grain structure in the as-cast state. After cold drawing, the recrystallization annealing temperature and holding time are adjusted to create a specific recrystallization texture in the tube. Through this microstructure control, the potential difference between the inner and outer surfaces of the tube is kept below 0.06V, thereby significantly improving corrosion resistance. Summary of the Invention
[0006] To address the aforementioned shortcomings, this invention provides a high-strength corrosion-resistant cupronickel tube and its preparation method. Through alloy composition optimization and multi-step texture control processes, the cupronickel tube forms a specific recrystallization texture, controlling the potential difference between the inner and outer surfaces to ≤0.06V. This solves the problem of severe galvanic corrosion and insufficient corrosion resistance caused by large potential differences in the prior art.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] A method for preparing a high-strength, corrosion-resistant cupronickel tube includes the following steps:
[0009] (1) Batching and smelting: Batching is carried out according to the mass fractions. Copper raw materials are put into an industrial frequency induction furnace and covered with charcoal covering agent for protection. The furnace temperature is raised to 1350℃~1400℃. After the furnace charge is completely melted, iron, cobalt, nickel and silicon copper, manganese copper and zinc copper intermediate alloys are added in sequence. 5~15 minutes before tapping, phosphorus copper, arsenic copper intermediate alloys and rare earth elements are added to adjust the composition and obtain cupronickel alloy melt.
[0010] (2) Horizontal continuous casting: The multi-phase phase diagram of the cupronickel alloy is calculated using the CALPHAD method to obtain the liquidus temperature range and solidus temperature range of the cupronickel alloy. Based on the calculated liquidus temperature and solidus temperature, the inlet temperature of the cooling water of the crystallizer is controlled at 20℃~30℃ and the casting speed is 100mm / min~300mm / min, so that the cooling rate of the ingot is controlled at 5℃ / s~15℃ / s, and the cupronickel tube billet is obtained.
[0011] (3) Homogenization heat treatment: The cupronickel tube blank is subjected to homogenization annealing treatment at a temperature of 860℃~920℃ and a holding time of 4~8 hours.
[0012] (4) Water seal extrusion: The tube blank after homogenization is heated to the extrusion temperature of 910℃~970℃, and after holding for 2~4 hours, water seal extrusion is performed. The extrusion ratio is 8~25, and the extrusion speed is 5mm / s~7mm / s. Before extrusion, high temperature glass lubricant is sprayed on the inner wall of the extrusion cylinder and the surface of the perforating needle.
[0013] (5) Multi-pass cold drawing: The extruded tube blank is subjected to multi-pass cold drawing, with a total deformation of 50% to 80% and the elongation coefficient of each pass controlled at 1.11 to 1.33. Intermediate annealing is performed between adjacent passes.
[0014] (6) Final annealing treatment: The cold-drawn pipe is subjected to final recrystallization annealing treatment under a protective atmosphere. The annealing temperature is 580℃~680℃ and the annealing time is 30~120 minutes. The annealing temperature and holding time are adjusted according to the target recrystallization texture type to form a recrystallization texture. After annealing, the pipe is cooled to room temperature by air cooling so that the potential difference between the inner and outer surfaces of the pipe is ≤0.06V.
[0015] Preferably, the preheating temperature of the extrusion cylinder for water sealing extrusion in step (4) is 350℃~450℃.
[0016] Preferably, the mold preheating temperature in step (4) is 400℃~500℃.
[0017] Preferably, in step (5), the deformation amount of a single pass in the multi-pass cold drawing is controlled at 10% to 25%, the intermediate annealing temperature is 620℃ to 700℃, and the holding time is 1 to 3 hours.
[0018] Preferably, the protective atmosphere in step (6) is nitrogen or argon.
[0019] A high-strength, corrosion-resistant cupronickel tube, by mass, comprises the following components: C: ≤0.03 parts; Si: 0.10–0.20 parts; Mn: 6.0–8.0 parts; S: ≤0.005 parts; P: 0.15–0.20 parts; Ni: 22.0–24.0 parts; Co: 2.0–4.0 parts; Zn: 2.0–4.0 parts; Pb: 0.20–0.40 parts; Fe: 3.0–4.0 parts; rare earth element RE: 0.15–0.20 parts; As: 0.005–0.010 parts; the balance being copper and unavoidable impurities. The potential difference between the inner and outer surfaces of the cupronickel tube is ≤0.06V, and the potential difference is measured using a saturated calomel electrode as a reference electrode in a 3.5wt% NaCl solution at 25℃±2℃.
[0020] Preferably, the rare earth element RE is cerium and / or lanthanum.
[0021] Preferably, the outer diameter of the cupronickel tube is 6mm to 159mm, with a tolerance of ±0.06mm to ±0.50mm; the wall thickness of the cupronickel tube is 0.5mm to 10mm, with a tolerance of ±0.03mm to ±0.80mm, and an eccentricity ≤8%; the length of the cupronickel tube is 20mm to 15000mm, with a tolerance ≤6.35mm; and the straightness deviation is ≤3mm / m.
[0022] Preferably, the tensile strength R of the cupronickel tube is... m ≥290MPa, specified non-proportional elongation strength R p 0.2≥105MPa, elongation after fracture A≥30%.
[0023] Preferably, the recrystallization texture of the cupronickel tube is {001}. <100> cubic texture and / or {011} <211> Brass texture.
[0024] Compared with the prior art, the present invention has the following advantages and technical effects:
[0025] I. Effective control of as-cast microstructure uniformity
[0026] Microscopic segregation of elements such as nickel, iron, and manganese in cupronickel alloys significantly affects the microstructure uniformity during subsequent processing and the corrosion resistance of the final product. While existing cupronickel tube manufacturing technologies have disclosed alloy composition ranges similar to those of this invention, none have proposed effective control measures for the microstructure uniformity of the ingot. Copper-nickel alloys are prone to dendritic segregation during solidification, and obvious banded segregation of nickel can be observed along the drawing direction. This segregation is difficult to completely eliminate during subsequent extrusion and drawing processes, ultimately leading to compositional and microstructural inhomogeneities in the tube's wall thickness direction.
[0027] This invention, in the horizontal continuous casting process, controls the inlet temperature of the cooling water in the crystallizer, the casting speed, and the ingot cooling rate to achieve a uniform composition and refined grain structure in the ingot during the solidification stage. The matching relationship between the inlet temperature of the cooling water in the crystallizer, the casting speed, and the ingot cooling rate directly affects the temperature gradient at the solid-liquid interface and the supercooling at the solidification front, thus determining the degree of segregation and grain size of the as-cast structure. Through the synergistic control of these three parameters, this invention ensures that the grain size of the solidified ingot is consistent from the surface to the core, effectively suppressing the formation of interdendritic segregation bands and eliminating the adverse effects of segregation on subsequent processing and the performance of the final product.
[0028] II. Texture Regulation and Electrochemical Uniformity
[0029] Current annealing processes for cupronickel tubes primarily aim to eliminate work hardening and restore plasticity. These processes are simplistic and lack directional control over texture type. Research indicates that the corrosion resistance of cupronickel alloy tubes is closely related to their surface microstructure. Grains with different crystallographic orientations exhibit anisotropic dissolution rates in sodium chloride solution. When the crystallographic orientations of the inner and outer surfaces of the tube are inconsistent, a potential difference forms between them, resulting in galvanic corrosion in seawater and accelerating localized corrosion.
[0030] In the final annealing process, this invention adjusts the annealing temperature and holding time according to the target recrystallization texture type to create a specific recrystallization texture in the pipe. By coordinating the annealing temperature and holding time, the recrystallized grains preferentially grow along a specific crystallographic direction during the growth process. This technique ensures that the crystallographic orientation of the inner and outer surfaces of the pipe is consistent, reducing the difference in electrochemical activity between the inner and outer surfaces, achieving precise control of the potential difference between the inner and outer surfaces, and transforming the corrosion morphology from localized corrosion to uniform corrosion, effectively suppressing pitting and crevice corrosion.
[0031] III. Systematic Optimization of the Preparation Process
[0032] White copper alloys are difficult to extrude due to their high heating temperature, high deformation resistance, and high viscosity. Existing manufacturing processes lack systematic optimization of key parameters such as extrusion temperature, extrusion speed, and elongation coefficient per pass, leading to unstable forming quality. This invention systematically limits the extrusion temperature, extrusion speed, extrusion ratio, and the preheating temperatures of the extrusion cylinder and die to ensure the stability of metal rheology during extrusion. The matching relationship between extrusion temperature, extrusion speed, and extrusion ratio directly determines the deformation uniformity and surface quality of the tube during extrusion.
[0033] In the multi-pass cold drawing process, this invention effectively avoids pipe cracking and surface quality deterioration caused by excessive deformation in a single pass by controlling the total deformation, pass elongation coefficient, and single-pass deformation, and by performing intermediate annealing between adjacent passes, thus ensuring the consistency of deformation on the inner and outer surfaces. Simultaneously, this invention adds a homogenization heat treatment step before extrusion, allowing alloying elements to fully diffuse in the matrix, further ensuring the uniformity of the pipe's microstructure. Cupronickel alloys have low stacking fault energy, making them prone to dislocation pile-ups and deformation bands during cold deformation. By rationally setting the intermediate annealing regime, the deformed microstructure recovers and recrystallizes before subsequent passes, avoiding pipe cracking caused by accumulated work hardening.
[0034] IV. Corrosion resistance in harsh marine environments
[0035] Traditional cupronickel pipes exhibit insufficient corrosion resistance in the high-salinity and high-temperature marine environment of the South China Sea. This is fundamentally due to the accelerated electrochemical corrosion kinetics of this environment, which places higher demands on the electrochemical uniformity of the pipe material. Existing domestically produced B10 and BFe30-1-1 alloys have not demonstrated ideal corrosion resistance in the South China Sea. This invention utilizes a comprehensive approach, including controlling the uniformity of the as-cast microstructure, eliminating segregation through homogenization heat treatment, ensuring consistent deformation of the inner and outer surfaces through multi-pass cold drawing, and reducing the potential difference between the inner and outer surfaces through texture control during the final annealing process. This effectively controls the potential difference between the inner and outer surfaces of the cupronickel pipe, significantly improving its corrosion resistance in the high-salinity and high-temperature marine environment of the South China Sea. Attached Figure Description
[0036] Figure 1 The changes in potential difference, corrosion rate and elongation after fracture of the alloy at different homogenization annealing temperatures are shown.
[0037] Figure 2 The changes in potential difference, corrosion rate and elongation after fracture of the alloy at different extrusion temperatures;
[0038] Figure 3 The changes in potential difference, corrosion rate and elongation after fracture of the alloy under different extrusion speeds;
[0039] Figure 4The changes in potential difference, corrosion rate and elongation after fracture of the alloy at different intermediate annealing temperatures are shown.
[0040] Figure 5 The changes in potential difference, corrosion rate and elongation after fracture of the alloy at different final annealing temperatures are shown.
[0041] Figure 6 The alloy of this invention exhibits an inhomogenized as-cast microstructure in the horizontal continuous casting state.
[0042] Figure 7 This is the backscattered SEM morphology of the Ce-La composite rare earth strip-shaped purification phase of the present invention;
[0043] Figure 8 This is a SEM image showing the overall distribution of the rare earth composite purification phase in the alloy matrix of this invention.
[0044] Figure 9 This is the CALPHAD phase diagram of the cupronickel alloy core system of this invention;
[0045] Figure 10 This is a projection diagram of the liquidus lines in a Cu-Ni-Fe ternary alloy. Detailed Implementation
[0046] The present invention will now be described in detail with reference to specific embodiments. These embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention. These all fall within the scope of protection of the present invention.
[0047] In this invention, a method for preparing a high-strength, corrosion-resistant cupronickel tube includes the following steps:
[0048] (1) Batching and smelting: Batching is carried out according to the mass fractions. Copper raw materials are put into an industrial frequency induction furnace and covered with charcoal covering agent for protection. The furnace temperature is raised to 1350℃~1400℃. After the furnace charge is completely melted, iron, cobalt, nickel and silicon copper, manganese copper and zinc copper intermediate alloys are added in sequence. 5~15 minutes before tapping, phosphorus copper, arsenic copper intermediate alloys and rare earth elements are added to adjust the composition and obtain cupronickel alloy melt.
[0049] (2) Horizontal continuous casting: The multi-phase phase diagram of the cupronickel alloy is calculated using the CALPHAD method to obtain the liquidus temperature range and solidus temperature range of the cupronickel alloy. Based on the calculated liquidus temperature and solidus temperature, the inlet temperature of the cooling water of the crystallizer is controlled at 20℃~30℃ and the casting speed is 100mm / min~300mm / min, so that the cooling rate of the ingot is controlled at 5℃ / s~15℃ / s, and the cupronickel tube billet is obtained.
[0050] (3) Homogenization heat treatment: The cupronickel tube blank is subjected to homogenization annealing treatment at a temperature of 860℃~920℃ and a holding time of 4~8 hours.
[0051] (4) Water seal extrusion: The tube blank after homogenization is heated to the extrusion temperature of 910℃~970℃, and after holding for 2~4 hours, water seal extrusion is performed. The extrusion ratio is 8~25, and the extrusion speed is 5mm / s~7mm / s. Before extrusion, high temperature glass lubricant is sprayed on the inner wall of the extrusion cylinder and the surface of the perforating needle.
[0052] (5) Multi-pass cold drawing: The extruded tube blank is subjected to multi-pass cold drawing, with a total deformation of 50% to 80% and the elongation coefficient of each pass controlled at 1.11 to 1.33. Intermediate annealing is performed between adjacent passes.
[0053] (6) Final annealing treatment: The cold-drawn pipe is subjected to final recrystallization annealing treatment under a protective atmosphere. The annealing temperature is 580℃~680℃ and the annealing time is 30~120 minutes. The annealing temperature and holding time are adjusted according to the target recrystallization texture type to form a recrystallization texture. After annealing, the pipe is cooled to room temperature by air cooling so that the potential difference between the inner and outer surfaces of the pipe is ≤0.06V.
[0054] The preheating temperature of the extrusion cylinder for water seal extrusion in step (4) is 350℃~450℃.
[0055] The mold preheating temperature in step (4) is 400℃~500℃.
[0056] In step (5), the deformation amount of a single pass in the multi-pass cold drawing is controlled at 10% to 25%, the intermediate annealing temperature is 620℃ to 700℃, and the holding time is 1 to 3 hours.
[0057] The protective atmosphere described in step (6) is nitrogen or argon.
[0058] A high-strength, corrosion-resistant cupronickel tube, by mass, comprises the following components: C: ≤0.03 parts; Si: 0.10–0.20 parts; Mn: 6.0–8.0 parts; S: ≤0.005 parts; P: 0.15–0.20 parts; Ni: 22.0–24.0 parts; Co: 2.0–4.0 parts; Zn: 2.0–4.0 parts; Pb: 0.20–0.40 parts; Fe: 3.0–4.0 parts; rare earth element RE: 0.15–0.20 parts; As: 0.005–0.010 parts; the balance being copper and unavoidable impurities. The potential difference between the inner and outer surfaces of the cupronickel tube is ≤0.06V, and the potential difference is measured using a saturated calomel electrode as a reference electrode in a 3.5wt% NaCl solution at 25℃±2℃.
[0059] The rare earth element RE is cerium and / or lanthanum.
[0060] The outer diameter of the cupronickel tube is 6mm to 159mm, with a tolerance of ±0.06mm to ±0.50mm; the wall thickness of the cupronickel tube is 0.5mm to 10mm, with a tolerance of ±0.03mm to ±0.80mm, and an eccentricity of ≤8%; the length of the cupronickel tube is 20mm to 15000mm, with a tolerance of ≤6.35mm; and the straightness deviation is ≤3mm / m.
[0061] The tensile strength R of the cupronickel tube m ≥290MPa, specified non-proportional elongation strength R p 0.2≥105MPa, elongation after fracture A≥30%.
[0062] The recrystallization texture of the cupronickel tube is {001}. <100> cubic texture and / or {011} <211> Brass texture.
[0063] The working mechanism of each step in this invention is as follows:
[0064] The cupronickel tube of this invention uses a Cu-Ni binary continuous solid solution as the matrix. Nickel increases the electrode potential of the copper matrix, reduces the electrochemical potential difference between the matrix and the corrosive medium, and decreases the driving force for anodic dissolution. When the nickel content is between 22.0 and 24.0 parts, the matrix obtains a stable single-phase face-centered cubic structure.
[0065] Iron partially dissolves in the matrix, resulting in solid solution strengthening, and partially accumulates at grain boundaries, reducing grain boundary energy, inhibiting abnormal grain growth during hot working, and promoting the formation of a dense oxide film on the surface to block chloride ion penetration. Manganese has both deoxidizing and solid solution strengthening functions; it combines with oxygen to form oxides that float and are removed, reducing the porosity of the ingot. Cobalt further increases the degree of lattice distortion in the solid solution while reducing the tendency for grain boundary segregation, maintaining the uniformity of chemical composition in the grain boundary region. Silicon and phosphorus synergistically deoxidize; phosphorus can also form stable compounds with low-melting-point impurities such as lead and bismuth, reducing the concentration of grain boundary segregation and decreasing intergranular corrosion sensitivity. Arsenic inhibits the selective dissolution of cupronickel, accumulates on the surface, alters the cathodic process kinetic parameters of the corrosion reaction, and slows down the corrosion process. Rare earth elements combine with oxygen and sulfur to form high-melting-point compounds that float and are removed, purifying the grain boundaries. During solidification, they accumulate at the solid-liquid front, producing compositional supercooling that promotes nucleation and refines grains. They also segregate at grain boundaries, reducing grain boundary energy and decreasing the adsorption of corrosive ions at the grain boundaries. Zinc further improves corrosion resistance and reduces production costs, while lead improves machinability. The combined effect of these elements results in a fine-grained structure, pure grain boundaries, and a uniform chemical composition distribution in the alloy.
[0066] During the smelting process, the order of adding materials follows the principle of adding high-melting-point elements first, followed by low-melting-point and volatile elements. The charcoal covering agent creates a reducing atmosphere on the surface of the melt, preventing atmospheric oxygen from transferring into the melt, while also adsorbing floating non-metallic inclusions.
[0067] In the horizontal continuous casting process, the liquidus and solidus temperatures are obtained by calculating the multi-phase phase diagram using the CALPHAD method, and the casting temperature regime is formulated accordingly. A moderate cooling rate avoids macroscopic segregation and grain coarsening caused by excessively slow cooling, and also avoids compositional undercooling and exacerbated microscopic segregation caused by excessively rapid cooling. Control of the cooling water temperature difference in the crystallizer ensures a reasonable temperature gradient along the radial direction of the ingot, which is beneficial for obtaining a uniform transition structure from columnar to equiaxed grains.
[0068] In the homogenization heat treatment step, dendritic segregation is unavoidable under non-equilibrium solidification conditions. Homogenization annealing increases the diffusion coefficient of each alloying element in the face-centered cubic copper matrix, solute atoms migrate from high-concentration areas to low-concentration areas until the compositional differences tend to disappear, residual non-equilibrium eutectic phase dissolves, grain boundaries tend to straighten, and casting stress is released through dislocation climb and slip.
[0069] In the water-sealed extrusion process, the face-centered cubic (FCC) cupronickel has a low stacking fault energy, making dynamic recrystallization easier to occur. The deformation energy is continuously consumed to obtain fine, dynamically recrystallized grains. A sufficient extrusion ratio ensures the pipe receives adequate hydrostatic pressure, breaking down and refining coarse grains. The extruded product is rapidly cooled in water immediately after leaving the die, preventing oxidation of the high-temperature pipe surface and avoiding oxide scale embedding. Simultaneously, the dynamically recrystallized structure is frozen to room temperature, inhibiting slow grain growth. Preheating the extrusion cylinder and die reduces the temperature difference between the billet and the tooling, preventing thermal shock that could cause tooling cracking and uneven deformation due to sudden surface temperature drops.
[0070] During the multi-pass cold drawing process, dislocations intersect, entangle, and pile up to form substructures, resulting in work hardening. The total deformation ensures that the tube obtains sufficient work hardening and refined substructure, providing sufficient deformation energy for recrystallization annealing. Intermediate annealing eliminates work hardening and restores the material's plasticity through atomic diffusion and dislocation rearrangement.
[0071] In the final recrystallization annealing step, deformation energy storage within the annealing temperature range drives recrystallization nucleation. Distortion-free nuclei preferentially form in the region with the highest distortion energy, and these nuclei migrate through the interface, engulfing the deformed matrix. By controlling the annealing temperature and holding time, the low stacking fault energy characteristics of cupronickel are utilized to induce a specific preferred orientation texture in the recrystallized grains. This texture exhibits high crystallographic symmetry, with minimal differences in electrochemical activity across different crystallographic directions. The orientation of exposed crystal faces on the inner and outer surfaces tends to be consistent, reducing the open-circuit potential difference in the corrosive medium, thereby effectively controlling the potential difference between the inner and outer surfaces.
[0072] To make the present invention more fully disclosed, more specific embodiments are described below.
[0073] I. Testing Methods
[0074] (1) Potential difference between the inner and outer surfaces of the pipe
[0075] The measurements were performed using an electrochemical workstation. A section of at least 50 mm in length was cut from the copper tube to be tested as a sample, and measurements were taken on both the outer and inner surfaces of the tube. The tests were conducted in a 3.5 wt% NaCl solution at 25℃ ± 2℃ using a three-electrode system: a saturated calomel electrode (SCE) as the reference electrode, a platinum electrode as the auxiliary electrode, and the surface of the copper tube to be tested as the working electrode (test area at least 1 cm²). 2 Before testing, the sample to be tested is immersed in NaCl solution and stabilized for 10 minutes. The open circuit potential (OCP) is then measured. At least three different locations are measured for each sample, and the average value is taken. The average open circuit potential of the outer surface and the average open circuit potential of the inner surface are obtained respectively. The absolute value of the difference between the two is calculated as the potential difference between the inner and outer surfaces of the pipe.
[0076] (2) Recrystallization texture
[0077] Electron backscatter diffraction (EBSD) was performed using a scanning electron microscope equipped with an electron backscatter diffraction system. Samples were taken from the copper tube under test and prepared as EBSD samples through mechanical and electrolytic polishing. The test parameters were: accelerating voltage 20 kV, scan step size 1 μm, and scan area 500 μm × 500 μm. The collected Kikuchi flower samples were calibrated using EBSD data analysis software to obtain the crystallographic orientation of each grain and calculate {001}. <100> cubic texture and {011} <211> The area fraction of the brass texture, with an orientation deviation angle within 15°, is considered.
[0078] (3) Corrosion resistance (corrosion rate)
[0079] Neutral salt spray (NSS) tests were conducted according to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test". The test solution was a 3.5 wt% NaCl solution, the test temperature was 35℃±2℃, continuous spraying was used, and compressed air atomization was employed. The salt spray deposition rate was controlled at 1.0 mL / 80 cm. 2 ·h~2.0mL / 80cm 2Between 10 and 12 hours. The samples are suspended inside the salt spray chamber, with the working surface at an angle of 15° to 30° to the vertical. The samples do not contact each other or the chamber body. The test period is 720 hours (30 days), and continuous spraying must not be interrupted during the test. After the test, the samples are removed, cleaned with deionized water, and dried. The corrosion rate is calculated using the weight loss method. The formula for calculating the corrosion rate is: Corrosion rate = (mass before test - mass after test) / (sample surface area × test time).
[0080] (4) Mechanical properties (elongation after fracture A)
[0081] The test was conducted on a universal testing machine in accordance with GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test at room temperature". The specimen was a longitudinally curved specimen cut from a cupronickel tube, with a gauge length of 50 mm. The tensile rate was 5 mm / min. The tensile test was carried out at room temperature until the specimen broke, and the elongation after fracture A was measured.
[0082] II. Implementation Examples
[0083] Example 1
[0084] A method for preparing a high-strength, corrosion-resistant cupronickel tube includes the following steps:
[0085] A high-strength, corrosion-resistant cupronickel tube with an outer diameter of 32 mm and a wall thickness of 3.0 mm was prepared. Its chemical composition by weight was: C 0.025 parts, Si 0.15 parts, Mn 7.0 parts, S 0.004 parts, P 0.18 parts, Ni 23.0 parts, Co 3.0 parts, Zn 3.0 parts, Pb 0.30 parts, Fe 3.5 parts, rare earth element RE (cerium) 0.18 parts, As 0.008 parts, with the balance being copper. The specific steps are as follows:
[0086] (1) Batching and smelting: Electrolytic copper is put into an industrial frequency induction furnace and covered with charcoal covering agent for protection. The furnace temperature is raised to 1380℃. After all the furnace charge has melted, industrial pure iron, electrolytic cobalt, electrolytic nickel and silicon copper master alloy (containing 20% Si), manganese copper master alloy (containing 25% Mn), zinc copper master alloy (containing 25% Zn) are added in sequence. 10 minutes before tapping, phosphorus copper master alloy (containing 15% P), arsenic copper master alloy (containing 10% As) and mixed rare earth (cerium) are added to adjust the composition and obtain cupronickel alloy melt.
[0087] (2) Horizontal continuous casting: The vertical section phase diagram of the core system of the cupronickel alloy calculated using the CALPHAD method is shown in the figure. Figure 9 The projection of the ternary liquidus line is shown in the figure. Figure 10The liquidus temperature of the alloy was obtained to be 1275℃ and the solidus temperature to be 1200℃. The molten cupronickel alloy was injected into a horizontal continuous casting mold for casting. The cooling water inlet temperature of the mold was controlled at 25℃ and the casting speed was 200mm / min, so that the cooling rate of the ingot was controlled at 10℃ / s, and a cupronickel tube billet with an outer diameter of 65mm and a wall thickness of 7.5mm was obtained.
[0088] (3) Homogenization heat treatment: The white copper tube blank is subjected to homogenization annealing treatment at a temperature of 890°C and a holding time of 6 hours.
[0089] (4) Water seal extrusion: The homogenized tube blank is heated to the extrusion temperature of 940℃ and kept at the temperature for 3 hours before water seal extrusion molding. The extrusion ratio is 9.5, the extrusion speed is 6mm / s, the extrusion cylinder preheating temperature is 400℃, the die preheating temperature is 450℃, and high temperature glass lubricant is sprayed on the inner wall of the extrusion cylinder and the surface of the perforating needle before extrusion to obtain an extruded tube blank with an outer diameter of 36mm and a wall thickness of 4.0mm.
[0090] (5) Multi-pass cold drawing: The extruded tube blank is subjected to 4 passes of cold drawing, with a total deformation of 65%. The elongation coefficients of the passes are 1.18, 1.21, 1.22 and 1.19 respectively. Intermediate annealing is performed between adjacent passes at a temperature of 660℃ and a holding time of 2 hours to obtain a tube with an outer diameter of 33mm and a wall thickness of 3.1mm.
[0091] (6) Final annealing treatment: The cold-drawn pipe is subjected to final recrystallization annealing treatment under nitrogen protective atmosphere. The annealing temperature is 630℃ and the holding time is 60 minutes. After annealing, it is cooled to room temperature by air cooling.
[0092] Metallographic and scanning electron microscopy characterization were performed on the continuously cast billet and finished pipe prepared in this embodiment. The non-homogenized billet showed obvious dendritic solute segregation, with morphology as shown in the figure. Figure 6 The Ce-La rare earth composite purification phase is dispersed in the matrix of the finished product. The overall distribution at low magnification is shown in the figure. Figure 8 The morphology of strip-shaped rare earth phases under high magnification is as follows Figure 7 The uniformly dispersed rare earth second phase can refine the grains, fix harmful impurities, and eliminate component segregation in the wall thickness, ultimately controlling the potential difference between the inner and outer surfaces of the pipe to within 0.06V, significantly improving its resistance to localized corrosion under marine conditions.
[0093] Key process single-factor experiment and result analysis
[0094] Based on the key process parameter range of this invention, single-factor experiments were designed around five core parameters: homogenization annealing temperature, extrusion temperature, extrusion speed, intermediate annealing temperature, and final annealing temperature. Each experiment was based on Example 1, and the test items were the same as in Example 1.
[0095] Single-factor experiment 1: Effect of homogenization annealing temperature on the microstructure and properties of cupronickel tubes
[0096] Based on Example 1, only the homogenization annealing temperature in step (3) was changed, while the other parameters remained unchanged.
[0097] Table 1. Performance test results at different homogenization annealing temperatures
[0098]
[0099] Results Analysis (Based on) Figure 1 ):
[0100] When the homogenization annealing temperature is 830℃, the diffusion rate of alloying elements in the matrix is insufficient, and dendritic segregation is not fully eliminated. The residual segregation bands are elongated during subsequent extrusion and drawing processes, resulting in non-uniform composition along the pipe wall thickness. An electrochemical potential difference exists between the segregated regions and the matrix, forming micro-polarity pairs in the corrosive medium, increasing the potential difference between the inner and outer surfaces of the pipe to 0.042V, and achieving a corrosion rate of 0.0168 mm / a.
[0101] When the temperature rises to 890℃, the alloying elements obtain sufficient diffusion activation energy, segregation is basically eliminated, and compositional uniformity is improved. The uniform microstructure ensures the consistency of deformation of the inner and outer surfaces of the tube during the subsequent cold drawing process. After final annealing, the potential difference drops to 0.014V, the corrosion rate drops to 0.0082mm / a, and the elongation after fracture reaches 36.5%, resulting in optimal overall performance.
[0102] When the temperature is further increased to 950℃, the excessively rapid atomic diffusion leads to abnormal grain coarsening. The coarse grain structure results in uneven deformation during cold drawing, producing different deformation texture components on the inner and outer surfaces of the tube. After annealing, the potential difference rises back to 0.032V. Simultaneously, the adverse effect of the coarse grain structure on plasticity reduces the elongation after fracture to 33.4%.
[0103] Single-factor experiment 2: Effect of extrusion temperature on the microstructure and properties of cupronickel tubes
[0104] Based on Example 1, only the extrusion temperature of the water seal extrusion in step (4) is changed, while the other parameters remain unchanged.
[0105] Table 2 Performance test results at different extrusion temperatures
[0106]
[0107] Results Analysis (Based on) Figure 2 ):
[0108] When the extrusion temperature is 880℃, the alloy exhibits high deformation resistance and poor plasticity. Excessively low extrusion temperatures prevent sufficient dynamic recrystallization, resulting in a deformed microstructure that retains high-density dislocations and subgrain boundaries. This inhomogeneous deformed microstructure leads to disordered grain orientation during final annealing, resulting in significant differences in crystallographic orientation between the inner and outer surfaces of the pipe, an increased potential difference to 0.056V, and a corrosion rate of 0.0206 mm / a. Simultaneously, insufficient plasticity reserve results in an elongation at fracture of only 27.8%.
[0109] When the extrusion temperature is increased to 940℃, the alloy is in its optimal hot working temperature range. At this temperature, the copper-nickel alloy, with its low stacking fault energy, undergoes sufficient dynamic recovery and recrystallization. Dynamic recrystallization refines the grains while eliminating deformation texture, providing a uniformly structured billet for subsequent cold drawing. After final annealing, the potential difference drops to 0.014V, resulting in optimal overall performance.
[0110] When the extrusion temperature rises to 1000℃, the excessively high temperature leads to abnormal growth of recrystallized grains. Simultaneously, the oxidation of the billet surface intensifies at high temperatures, and the resulting oxide layer is difficult to completely remove during subsequent processing. Residual surface defects become preferential sites for corrosion initiation. The combined effect of the coarse-grained structure and surface defects causes the potential difference to rise back to 0.048V, the corrosion rate to increase to 0.0184 mm / a, and the elongation after fracture to decrease to 29.6%.
[0111] Single-factor experiment 3: Effect of extrusion speed on the microstructure and properties of cupronickel tubes
[0112] Based on Example 1, only the extrusion speed of water seal extrusion in step (4) is changed, while the other parameters remain unchanged.
[0113] Table 3 Performance test results at different extrusion speeds
[0114]
[0115] Results Analysis (Based on) Figure 3 ):
[0116] Extrusion speed indirectly regulates the microstructure of the tube by affecting the deformation heat effect and the uniformity of metal flow. When the extrusion speed is 4.0 mm / s, the tube blank stays in the extrusion cylinder for too long, and the heat loss causes the actual deformation temperature to be lower than expected. The temperature drop leads to poor alloy fluidity, uneven metal flow, and inconsistent deformation between the inner and outer walls of the tube. This uneven deformation is transmitted to the final product, causing a potential difference of 0.036V.
[0117] When the extrusion speed is increased to 6.0 mm / s, the deformation heat effect and die heat dissipation reach a dynamic balance, and the billet temperature stabilizes within the optimal deformation range. The appropriate deformation rate promotes full dynamic recrystallization, resulting in uniform deformation across the pipe cross-section, and the potential difference drops to 0.014V after final annealing.
[0118] When the extrusion speed is too high, reaching 8.0 mm / s, the deformation time of the metal within the extrusion cylinder is too short, resulting in insufficient dynamic recrystallization. Simultaneously, high-speed extrusion leads to uneven temperature distribution at the metal flow front, increasing the difference in strain rates between the inner and outer walls of the pipe, and causing the deformed microstructure to exhibit an uneven distribution along the wall thickness direction. This inhomogeneity causes the potential difference to surge to 0.052 V, the corrosion rate to reach 0.0194 mm / a, and the elongation after fracture to decrease to 28.4%.
[0119] Single-factor experiment 4: Effect of intermediate annealing temperature on the microstructure and properties of cupronickel tubes
[0120] Based on Example 1, only the temperature of the intermediate annealing between adjacent passes in step (5) is changed, while the other parameters remain unchanged.
[0121] Table 4 Performance test results at different intermediate annealing temperatures
[0122]
[0123] Results Analysis (Based on) Figure 4 ):
[0124] When the intermediate annealing temperature is 580℃, only partial recovery of the cold-deformed structure occurs, and recrystallization is insufficient. The cumulative effect of work hardening results in insufficient plasticity of the pipe during subsequent cold drawing passes, making it prone to microcrack initiation. These defects become preferential sites for corrosion initiation in the final product, with the potential difference increasing to 0.040V.
[0125] When the intermediate annealing temperature is increased to 660℃, the cold-deformed structure undergoes full recrystallization, the dislocation density is significantly reduced, and the grains become finer and more uniform. The plasticity of the tube is fully restored, the subsequent cold drawing deformation is uniform, and the potential difference drops to 0.014V after final annealing.
[0126] When the intermediate annealing temperature was further increased to 740℃, the recrystallized grains became significantly coarser. The coarsened grains changed their deformation behavior during the subsequent cold drawing process, and the difference in deformation between the near-surface grains and the core grains increased, affecting the uniformity of the texture during the final annealing, and the potential difference rose back to 0.030V.
[0127] Single-factor experiment 5: Effect of final annealing temperature on the microstructure and properties of cupronickel tubes
[0128] Based on Example 1, only the temperature of the final recrystallization annealing in step (6) was changed, while the other parameters remained unchanged.
[0129] Table 5 Performance test results at different final annealing temperatures
[0130]
[0131] Results Analysis (Based on) Figure 5 ):
[0132] When the final annealing temperature is 530℃, the annealing temperature is too low, and the recrystallization driving force is insufficient to overcome the energy barrier for grain boundary migration. The cold-deformed structure only partially recovers. The deformation texture is largely retained, the crystallographic orientation difference between the inner and outer surfaces of the pipe is large, the potential difference is as high as 0.078V, the corrosion rate reaches 0.0308mm / a, and the elongation after fracture is only 16.2%.
[0133] When the final annealing temperature is raised to 630℃, recrystallization proceeds fully. The nucleation cores with specific orientations formed during cold deformation gain sufficient growth driving force and grow preferentially, resulting in a uniform crystallographic orientation on the inner and outer surfaces of the pipe, and the potential difference drops to 0.014V.
[0134] When the final annealing temperature rises to 730℃, the recrystallization grain boundary migration rate becomes too fast. The excessively high temperature causes secondary recrystallization of the grains, with some oriented grains growing abnormally and engulfing surrounding grains, disrupting the texture equilibrium established by the initial recrystallization, and the potential difference rises back to 0.032V.
[0135] Example 2
[0136] A method for preparing a high-strength, corrosion-resistant cupronickel tube includes the following steps:
[0137] The alloy composition is the same as in Example 1. The preparation method is the same as in Example 1 except for the following parameters:
[0138] In step (2): the casting speed is 150 mm / min, the cooling rate is 8℃ / s, and the inlet temperature of the cooling water for the crystallizer is 22℃.
[0139] In step (3): the homogenization annealing temperature is 870℃ and the holding time is 7 hours.
[0140] In step (4): the extrusion temperature is 920℃, the extrusion speed is 5.5mm / s, and the extrusion ratio is 9.8.
[0141] In step (5): the total deformation is 58%, the pass elongation coefficients are 1.15, 1.18, 1.20 and 1.16 respectively, the intermediate annealing temperature is 650℃ and the holding time is 2.5 hours.
[0142] In step (6): the annealing temperature is 620℃ and the holding time is 90 minutes.
[0143] Example 3
[0144] A method for preparing a high-strength, corrosion-resistant cupronickel tube includes the following steps:
[0145] The alloy composition is the same as in Example 1. The preparation method is the same as in Example 1 except for the following parameters:
[0146] In step (2): the casting speed is 250 mm / min, the cooling rate is 13℃ / s, and the inlet temperature of the cooling water for the crystallizer is 28℃.
[0147] In step (3): the homogenization annealing temperature is 920℃ and the holding time is 5 hours.
[0148] In step (4): the extrusion temperature is 960℃, the extrusion speed is 6.8mm / s, and the extrusion ratio is 9.2.
[0149] In step (5): the total deformation is 72%, the pass elongation coefficients are 1.22, 1.24, 1.26 and 1.22 respectively, the intermediate annealing temperature is 700℃ and the holding time is 1.5 hours.
[0150] In step (6): the annealing temperature is 680℃ and the holding time is 40 minutes.
[0151] Example 4
[0152] A method for preparing a high-strength, corrosion-resistant cupronickel tube includes the following steps:
[0153] The alloy composition is the same as in Example 1. The preparation method is the same as in Example 1 except for the following parameters:
[0154] In step (2): the casting speed is 120 mm / min, the cooling rate is 7℃ / s, and the inlet temperature of the cooling water for the crystallizer is 21℃.
[0155] In step (3): the homogenization annealing temperature is 860℃ and the holding time is 7.5 hours.
[0156] In step (4): the extrusion temperature is 910℃, the extrusion speed is 5.2mm / s, and the extrusion ratio is 10.2.
[0157] In step (5): the total deformation is 62%, the pass elongation coefficients are 1.16, 1.19, 1.21 and 1.18 respectively, the intermediate annealing temperature is 640℃ and the holding time is 2.8 hours.
[0158] In step (6): the annealing temperature is 600℃ and the holding time is 100 minutes.
[0159] Example 5
[0160] A method for preparing a high-strength, corrosion-resistant cupronickel tube includes the following steps:
[0161] The alloy composition is the same as in Example 1. The preparation method is the same as in Example 1 except for the following parameters:
[0162] In step (2): the casting speed is 280 mm / min, the cooling rate is 14℃ / s, and the inlet temperature of the cooling water for the crystallizer is 29℃.
[0163] In step (3): the homogenization annealing temperature is 920℃ and the holding time is 4.5 hours.
[0164] In step (4): the extrusion temperature is 970℃, the extrusion speed is 7.0mm / s, and the extrusion ratio is 8.8.
[0165] In step (5): the total deformation is 55%, the pass elongation coefficients are 1.14, 1.16, 1.18 and 1.15 respectively, the intermediate annealing temperature is 700℃ and the holding time is 1.2 hours.
[0166] In step (6): the annealing temperature is 680℃ and the holding time is 35 minutes.
[0167] Comparative Example 1
[0168] The same alloy composition as in Example 1 was used, and the preparation method was the same as in Example 1 except for the following parameters: the liquidus temperature and solidus temperature were not calculated using the CALPHAD method in step (2), the inlet temperature of the cooling water in the crystallizer was 35°C, the casting speed was 350 mm / min, and the ingot cooling rate was 18°C / s.
[0169] Comparative Example 2
[0170] The same alloy composition as in Example 1 was used. The extrusion temperature of water-sealed extrusion in step (4) of the preparation method was 850°C and the extrusion speed was 9 mm / s. The other parameters were the same as in Example 1.
[0171] Comparative Example 3
[0172] Using the same alloy composition as in Example 1, the annealing temperature of the final annealing treatment in step (6) of the preparation method is 480°C and the holding time is 180 minutes. The other parameters are the same as in Example 1.
[0173] Comparative Example 4
[0174] Commercially available BFe30-1-1 iron-copper tube (outer diameter 32mm, wall thickness 3.0mm, supplied in annealed state) was used as comparative example 4. Its chemical composition, according to GB / T 5231-2022, is as follows: Ni 29%~32%, Fe 0.5%~1.0%, Mn 0.5%~1.0%, with the balance being copper.
[0175] Summary of experimental results:
[0176] (a) Test Results
[0177] Table 6 Performance test results of each embodiment and comparative example
[0178]
[0179] (II) Data Comparison and Analysis (Based on Table 6)
[0180] (1) Potential difference analysis of inner and outer surfaces of pipe
[0181] The potential difference in Examples 1-5 was controlled between 0.014V and 0.018V. The potential difference in Comparative Examples 1-4 all exceeded 0.06V, with Comparative Example 4 reaching the highest of 0.092V and Comparative Example 1 having the lowest of 0.062V.
[0182] The electrochemical behavior of different crystal planes of copper-nickel alloys in sodium chloride solution exhibits anisotropy. The {001} crystal plane has a higher atomic packing density and lower surface energy, resulting in a more dense and stable passivation film. In contrast, the {011} and {211} crystal planes show stronger chloride ion adsorption activity. This invention, through the coordination of annealing temperature and holding time in the final annealing step, achieves a clear preferred growth direction for the recrystallized grains, resulting in similar texture composition on the inner and outer surfaces of the pipe. This leads to a convergence of corrosion potentials on the inner and outer surfaces, thereby reducing the potential difference.
[0183] Comparative Example 1, due to improper solidification parameters during continuous casting, resulted in dendritic segregation in the ingot that could not be eliminated during subsequent processing. The residual segregation bands created a pinning effect on the migration of recrystallization grain boundaries, inhibiting the preferred orientation of grains. This led to significant differences in texture composition between the inner and outer surfaces, with the potential difference increasing to 0.062V. Comparative Example 2, due to excessively low extrusion temperature, resulted in high deformation resistance and uneven metal flow during extrusion, leading to a scattered distribution of recrystallized grain orientation and a potential difference reaching 0.072V. Comparative Example 3, due to excessively low final annealing temperature, suffered from insufficient recrystallization driving force, resulting in only partial recovery of the cold-deformed structure and significant retention of the deformed texture, with a potential difference as high as 0.088V. Comparative Example 4, a commercially available BFe30-1-1 iron-copper tube, exhibited a random grain orientation and showed the greatest difference in electrochemical activity between the inner and outer surfaces, with a potential difference reaching 0.092V.
[0184] (2) Corrosion rate analysis
[0185] The corrosion rates of Examples 1-5 ranged from 0.0071 mm / a to 0.0103 mm / a, which was at a low level. The corrosion rates of Comparative Examples 1-4 ranged from 0.0235 mm / a to 0.0352 mm / a, which were significantly higher than those of Examples 1-5.
[0186] There is a positive correlation between potential difference and corrosion rate, essentially because the potential difference constitutes the driving force for galvanic corrosion. When a potential difference exists between the inner and outer surfaces of a pipe, a corrosion micro-cell is formed in the sodium chloride solution. The surface with the lower potential acts as the anode, undergoing a metal dissolution reaction, while the surface with the higher potential acts as the cathode, undergoing an oxygen reduction reaction. The greater the potential difference, the higher the corrosion current density, and the faster the metal dissolution rate.
[0187] In Examples 1-5, the potential difference was below 0.02V, resulting in minimal driving force for galvanic corrosion. The corrosion process was predominantly uniform, and the corrosion rate remained low. In Comparative Examples 1-4, the potential difference exceeded 0.06V, with Comparative Example 4 reaching 0.092V, exhibiting a significant galvanic corrosion effect and a corrosion rate of 0.0318 mm / a. As shown in Table 6, the corrosion rate increased with the potential difference from 0.014V to 0.092V, demonstrating a clear positive correlation. This invention effectively suppressed the galvanic corrosion effect by controlling the potential difference to a low level below 0.02V, transforming the corrosion morphology from localized corrosion to uniform corrosion, thus significantly improving corrosion resistance.
[0188] (3) Analysis of elongation after fracture
[0189] The elongation after fracture of Examples 1-5 ranged from 32.8% to 39.0%, all greater than 30%, meeting the technical requirements of the project task book. The elongation after fracture of Comparative Examples 1-4 ranged from 18.4% to 32.1%, with Comparative Example 3 at only 18.4% and Comparative Example 2 at 28.6%, both lower than the lowest values of the embodiments of the present invention.
[0190] Homogenization heat treatment essentially eliminates dendritic segregation in the as-cast state, ensuring uniform distribution of alloying elements within the matrix and preventing segregation bands from becoming stress concentration sources during cold drawing. Intermediate annealing between multiple cold drawing passes allows for the recovery and recrystallization of the deformed structure, eliminating accumulated work hardening and restoring the pipe's plastic deformation capacity.
[0191] Comparative Example 1, due to improper continuous casting parameters, had residual segregation bands that became crack initiation sites during stretching, resulting in an elongation at fracture of only 32.1%. Comparative Example 2, due to excessively low extrusion temperature, developed surface microcracks in the billet. These microcracks propagated rapidly during stretching, resulting in an elongation at fracture of only 28.6%, failing to meet the 30% requirement. Comparative Example 3, due to insufficient final annealing temperature, retained a large amount of deformation texture and dislocation entanglement, severely hindering dislocation movement and significantly reducing plasticity to 18.4%. Comparative Example 4, using commercially available BFe30-1-1, had an elongation at fracture of 31.2%, reaching 30%, but its overall corrosion resistance was far inferior to the embodiments of this invention.
[0192] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.
Claims
1. A method for preparing a high-strength, corrosion-resistant cupronickel tube, characterized in that, Includes the following steps: (1) Batching and smelting: Batching is carried out according to the mass fraction. Copper raw materials are put into the industrial frequency induction furnace and covered with charcoal covering agent for protection. The furnace temperature is raised to 1350℃~1400℃. After the furnace charge is completely melted, iron, cobalt, nickel and silicon copper, manganese copper and zinc copper intermediate alloys are added in sequence. 5~15 minutes before tapping, phosphorus copper, arsenic copper intermediate alloys and rare earth elements are added to adjust the composition and obtain cupronickel alloy melt. (2) Horizontal continuous casting: The multi-phase phase diagram of the cupronickel alloy is calculated using the CALPHAD method to obtain the liquidus temperature range and solidus temperature range of the cupronickel alloy. Based on the calculated liquidus temperature and solidus temperature, the inlet temperature of the cooling water of the crystallizer is controlled at 20℃~30℃ and the casting speed is 100mm / min~300mm / min, so that the cooling rate of the ingot is controlled at 5℃ / s~15℃ / s, and the cupronickel tube billet is obtained. (3) Homogenization heat treatment: The cupronickel tube blank is subjected to homogenization annealing treatment at a temperature of 860℃~920℃ and a holding time of 4~8 hours. (4) Water seal extrusion: The tube blank after homogenization is heated to the extrusion temperature of 910℃~970℃, and after holding for 2~4 hours, water seal extrusion is performed. The extrusion ratio is 8~25, the extrusion speed is 5mm / s~7mm / s, the preheating temperature of the extrusion cylinder is 350℃~450℃, the preheating temperature of the die is 400℃~500℃, and high temperature glass lubricant is sprayed on the inner wall of the extrusion cylinder and the surface of the perforating needle before extrusion. (5) Multi-pass cold drawing: The extruded tube blank is subjected to multi-pass cold drawing, with a total deformation of 50% to 80% and the elongation coefficient of each pass controlled at 1.11 to 1.
33. Intermediate annealing is performed between adjacent passes. (6) Final annealing treatment: The cold-drawn pipe is subjected to final recrystallization annealing treatment under a protective atmosphere. The annealing temperature is 580℃~680℃ and the annealing time is 30~120 minutes. The annealing temperature and holding time are adjusted according to the target recrystallization texture type to form a recrystallization texture. After annealing, the pipe is cooled to room temperature by air cooling so that the potential difference between the inner and outer surfaces of the pipe is ≤0.06V. The high-strength corrosion-resistant cupronickel tube, by mass, comprises the following components: C: ≤0.03 parts; Si: 0.10-0.20 parts; Mn: 6.0-8.0 parts; S: ≤0.005 parts; P: 0.15-0.20 parts; Ni: 22.0-24.0 parts; Co: 2.0-4.0 parts; Zn: 2.0-4.0 parts; Pb: 0.20-0.40 parts; Fe: 3.0-4.0 parts; rare earth element RE: 0.15-0.20 parts; As: 0.005-0.010 parts; the balance being copper and unavoidable impurities. The potential difference between the inner and outer surfaces of the cupronickel tube is ≤0.06V, and the potential difference is measured using a saturated calomel electrode as a reference electrode in a 3.5wt% NaCl solution at 25℃±2℃. The rare earth element RE is cerium and / or lanthanum.
2. The method for preparing high-strength corrosion-resistant cupronickel tube according to claim 1, characterized in that, In step (5), the deformation of a single pass in the multi-pass cold drawing is controlled at 10% to 25%; the temperature for intermediate annealing between adjacent passes is 620℃ to 700℃, and the holding time is 1 to 3 hours.
3. The method for preparing high-strength corrosion-resistant cupronickel tube according to claim 1, characterized in that, The protective atmosphere described in step (6) is nitrogen or argon.
4. A high-strength, corrosion-resistant cupronickel tube prepared according to any one of claims 1 to 3, characterized in that, The outer diameter of the cupronickel tube is 6mm to 159mm, with a tolerance of ±0.06mm to ±0.50mm; the wall thickness of the cupronickel tube is 0.5mm to 10mm, with a tolerance of ±0.03mm to ±0.80mm, and an eccentricity of ≤8%; the length of the cupronickel tube is 20mm to 15000mm, with a tolerance of ≤6.35mm; and the straightness deviation is ≤3mm / m.
5. The high-strength corrosion-resistant cupronickel tube according to claim 4, characterized in that, The tensile strength R of the cupronickel tube m ≥290MPa, specified non-proportional elongation strength R p 0.2≥105MPa, elongation after fracture A≥30%.
6. The high-strength corrosion-resistant cupronickel tube according to claim 5, characterized in that, The recrystallization texture of the cupronickel tube is {001}. <100> cubic texture and / or {011} <211> Brass texture.
Citation Information
Patent Citations
A corrosion-resistant cupronickel tube and its preparation method
CN103740977B
A short-process production method for large-diameter thin-walled copper-nickel tubes
CN105312353B
Large seamless cupronickel pipe and production method thereof
CN110961485A